Atypical Non-H2S-producing monophasic salmonella typhimurium ST3478 strains from chicken meat at processing stage are adapted to diverse stresses - Mourão, Joana (2020)
Poultry products are still an important cause of Salmonella infections worldwide, with an increasingly reported expansion of less-frequent serotypes or atypical strains that are frequently multidrug-resistant. Nevertheless, the ability of Salmonella to survive antimicrobials promoted in the context of antibiotic reducing/replacing and farming rethinking (e.g., organic acids and copper in feed/biocides) has been scarcely explored. We investigated Salmonella occurrence (conventional and molecular assays) among chicken meat at the processing stage (n = 53 batches/29 farms) and characterized their tolerance to diverse stress factors (antibiotics, copper, acid pH, and peracetic acid).